Exploring the Benefits of NSS Participation for Undergraduates in Indian Universities: A Case Study - Mallesha, C.; Madhu, S. (Journal of Engineering Education Transformations, 2025)
This study examines the benefits of NSS membership for Indian undergraduates at Anurag University. The Ministry of Youth Affairs and Sports founded the NSS in 1969 to promote student social welfare and civic responsibility via community service. The study examines how NSS activities affect students' civic responsibility, leadership, and community engagement. The mixed-methods study collected quantitative data through questionnaires and qualitative data through focus group discussions and student and program coordinator interviews. The quantitative research demonstrated significant increases in students' social awareness, community leadership confidence and volunteerism. Qualitative research showed that NSS activities made students more socially aware, confident and eager to help society. The study identifies that NSS improves students' civic responsibility, leadership and community engagement, according to the study. These findings can help optimize NSS programs for comprehensive student development and social progress.